Exponential stabilization of chaotic systems based on fuzzy time-triggered intermittent control. (September 2022) - Peng, Shuo; Wang, Qingzhi; Fu, Baozeng
Abstract: The exponential stabilization of chaotic systems is studied via fuzzy time-triggered intermittent control (FTIC). For the Takagi-Sugeno (T-S) fuzzy model representing a chaotic system, the mathematical description of FTIC is presented initially. Compared with fuzzy intermittent control (FIC), FTIC just needs the information at sampling instants on control time intervals. Compared with fuzzy sampled-data control (FSC), FTIC only transmits partial sampling data. Then, for the deduced FTIC system, a novel mixed Lyapunov functional is constructed to establish an exponential stabilization theorem. Based on it, FTIC can be designed. Further, the amount of transmitted data and the cost function are considered as two performance indexes. Finally, the inverted pendulum system and the chaotic Lorenz system are taken as examples to show the effectiveness and superiority of FTIC.